Spectrophotometric Titration of Resorufin and Resazurinwith Iron(II) in Strong Phosphoric Acid Medium and Resorufin as a New Redox Indicator in the ReductimetricTitration of Some Metal Ions - RAJU, K.VIJAYA; DAVID SUDHAKAR, G.; BENARJI PATRUDU, T. (Asian Journal of Chemistry, 2010)
Spectrophotometric titration methods have been developed for the determination of micro-gram quantities of resazurin and resorufin and the analysis of their binary mixture using iron(II) as a reductant in high concentration of orthophosphoric acid (10.5 M) medium. Both resazurin and resorufin are reduced to a blue-green semiquinone (λmax 640 nm) with iron(II) in three electrons and one electron reduction steps respectively. Resorufin has been proposed as a new advantageous redox indicator in the determination ofV(V), V(IV), Mo(VI), Cr(VI), Cu(II), Sb(V), As(V), Os(VIII) and Ir(IV) in phosphoric acid medium using the same reductant.